SIFAT VENIR DAN KAYU LAPIS DARI KAYU SENGON DAN KARET PADA BEBERAPA MACAM UMUR - M I Iskandar; Suwandi Kliwon; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
The result of the suitability study of two wood species as raw material for veneer and plywood are reported. The wood raw material used rubber wood (Hevea brasiliensis) and sengon (Paraserianthes falcataria). The wood used were obtained from different age classes i.e.10 and 20 years for rubber wood and 10 and 15 years for sengon. The study consisted of log peeling characteristic, veneer properties and some physical-mechanical properties of plywood (triplex and multiplex).All of the logs from two wood species could be peeled in cold condition, producing 1,5 mm veneer at a cutting angle between 89o30'-91o30'. The average shrinkage of veneer is 4.51% and the average veneer swelling from oven-dry to air dry is 3.30 %.The bonding strength of plywood from all wood species conform with the Indonesian standard, German standard and Japanese standard for type 11 or water resistant. The spesific gravity and mechanical properties of plywood from the older tree tends higher than that from the younger tree.